The surprising gospel intriguing psychological insights from the New Testament - Wuellner, Willhelm H. 1927-; Leslie, Robert Campbell, 1917- (Nashville, TN Abingdon, 1984)
Includes bibliographical references and index.
Keywords: Bible. N.T. -- psychology